Diamond microcrystallites formation through the phase transition graphite→liquid→diamond - Semikina, T.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
The paper presents the results of synthesizing the diamond microparticles (3 to 5 µm) in a spark discharge in hydrogen at the low pressure (100 Torr). The obtained growth rate ~5 µm/s is uniquely high. Our analysis of the nature of particles by using SEM and Raman spectroscopy demonstrates that these particles are cubic high quality diamond. Using the result of SIM images after cross-cutting of the sample by FIB, it is concluded that diamond does not grow on the substrate and running process is not CVD. Discussing the theory of the spark discharge, it is suggested that the process occurs at high pressures and temperatures. A hypothesis of diamond formation through a diffusion mechanism of the direct phase transition is presented.